The Power of Supply and Demand : Thinking Tools and Case Studies for Students and Professionals - Lai, Wai-chung, Lawrence, 1959- (Book collections on Project MUSE., 2006)
Key Points 1. An effective guide to the economics of property rights; 2. An overview of the power of economic analysis and its foundations; 3. A companion for business and development practitioners; 4. A set of tools for meaningful discussion of government policies and law; 5. A must for economics teachers.